The Role of Parents in Children Memorizing the Qur'an in Middle School Based on the Amanatul Ummah Islamic Boarding School - Mizanul Hasanah (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
This article originated from the author's curiosity about the close inner relationship between parents and children who memorize the Qur'an. For the author of the Qur'an, it is Allah's revelation that was sent down directly to Rasulullah Muhammad SAW through the angel Gabriel. For this reason, the holy book of the Qur'an, which is very sacred and is the word of Allah, cannot be memorized if the individual does not appreciate, understand the signs, and glorify Allah before reading and memorizing it. One of them is filial piety to parents and do good to them. The author conducted direct research on the right target, namely the children who memorized the Quran in SMP-based Pesantren Amanatul Ummah Pacet. The aim of the author to conduct research at this location is that the children in the institution focus on producing Al-Quran memorizers. The method used in this research is descriptive qualitative research. Sources of data used are primary and secondary data sources and use data collection techniques in the form of interviews, observation, and documentation.